A new heuristic reconfiguration algorithm for large distribution systems - Gomes, F.V.; Carneiro, S.; Pereira, J.L.R.; Vinagre, M.P.; Garcia, P.A.N.; Araujo, L.R. (IEEE transactions on power systems, 2005)
This paper presents a reconfiguration algorithm that is specially suited to large-scale distribution systems. The algorithm uses a heuristic strategy that starts with the system in a meshed status, with all maneuverable switches closed. The choice of the switches to be opened is based on the calculation of the minimum total system losses, using a load-flow program. A refinement on this procedure, based on branch status exchange, is described. The paper includes results and comparisons on test systems utilized in three classical papers published in the technical literature. Results obtained on a real large-scale distribution system are also presented.